The first analysis of the outward H fluxes measured by IBEX-Lo in 20–50 RE geocentric distances - Park, Jeewoo; Connor, Hyunju K. (Frontiers in Astronomy and Space Sciences, 2025)
In this study, we analyze the energetic neutral atom (ENA) observations measured in the lowest energy channel (10–21 eV) of the IBEX-Lo instrument on Interstellar Boundary Explorer (IBEX) during two spring seasons, day of year (DOY) 101–146, 2009, and DOY 88–178, 2013, confirming the existence of outward hydrogen (H) fluxes at 15 eV. The outward H flux decreases slightly with distance, showing an intensity of approximately 106 cm−2 s−1 sr−1 keV−1. Results also suggest that the outward H fluxes are not influenced by solar radio flux. We compute the expected H ENA fluxes at 15 eV using ion flux measurements from the Helium, Oxygen, Proton, and Electron (HOPE) mass spectrometer aboard the Radiation Belt Storm Probes (RBSP) during the corresponding period of the 2013 spring season, combined with a simple exospheric density model (nH=nH0r0/r3, where r0=10 RE). The expected ENA fluxes similarly show a decrease in the intensity with increasing geocentric distance, which is on the order of 105–106 cm-2 s−1 sr−1 keV−1. These consistent features suggest that the outward H fluxes observed by IBEX-Lo are closely related to escaping H ENAs produced within the inner exosphere (<4 RE).